Menjaga kualitas layanan, membangun kepercayaan: Strategi perbankan syariah dalam manajemen risiko reputasi - Ayu, Diyah Isthi (Maliki Interdisciplinary Journal, 2024)
A good reputation, Islamic banks will gain trust, loyal customers, and will even have an impact on good profit growth. Reputation risk also usually occurs when there is a negative assessment from customers either caused by customer disappointment. The purpose of this study is to analyze the urgency of reputation risk management in Islamic banks. This type of research is qualitative research with a literature review approach with data collection techniques using search engines on Google Scholar. The results of the literature study obtained are that reputation risk is not far from the effectiveness of the supervisory role of the Board of Commissioners, Directors, and Sharia Supervisory Board, and being able to recruit qualified Human Resources to bring Islamic Banks to be more competitive in sophisticated conditions. Reputation risk has a risk management strategy and some reputation risk issues also have a risk level, namely Risk Appetite (risk to be taken) and Risk Tolerance (risk tolerance). Translated with DeepL.com (free version).